Methods Of Kinematic Study of Flat Base Mechanisms (Texas Journal of Multidisciplinary Studies, 2021)
The article covers the method for determining linear velocities and accelerations of individual points and angular velocities and accelerations of links for mechanisms with lower kinematic couples, which are widely used in many industry branches due to reliability, technological effectiveness and ability to transmit great loads.